PROBLEMS OF IMPROVING THE TERRITORIAL COMPOSITION OF INDUSTRY DEVELOPMENT - Torabekova Gulirano Islamovna (EPRA International Journal of Research and Development (IJRD), 2023)
In the article It was revealed that it is necessary to give priority to the development of scientific and technical development and industrial sectors that produce consumer goods, as well as to strengthen the influence of the sectors that determine scientific and technical and innovative development, which are the foundation of the national economy.